Prevalence of mental disorders at admission to the penal justice system in emerging countries: a study from Chile. (19th June 2015) - Mundt, A. P.; Kastner, S.; Larraín, S.; Fritsch, R.; Priebe, S.
Abstract : Background: Previous mental health surveys conducted in prisons within emerging countries recruited samples of all prisoners at any single point in time. However, this sampling strategy results in an overrepresentation of long-term prisoners as compared with those studies recruiting from all admissions over time. This study aimed to assess mental disorders in consecutively admitted prisoners soon after admission, in order to address service needs of people with short-term imprisonments and people at early stages of imprisonment. Method: Disorders were assessed in a sample of 229 male and 198 female prisoners, consecutively committed to the penal justice system in Santiago de Chile, using the structured Mini-Neuropsychiatric interview. Prevalence rates were calculated as per cent values. Ninety-five per cent confidence intervals were calculated for the proportions. Results: Illicit drug and/or alcohol use disorders in the year prior to admission were present in 173 (76%) male and 64 (32%) female prisoners. The substances most frequently causing addiction were cocaine-based products in 108 (47%) male and 42 (21%) female prisoners. Current major depression was present in 124 (54%) male and 86 (43%) female prisoners, and current non-affective psychotic disorders in 18 (8%) male and in 10 (5%) female prisoners. High suicidal risk was present in 64 (28%) male prisoners and in 29 (15%) female prisoners. Conclusion: When consecutive prisoners are assessed at admission, rates of mental health and substance use disorders were higher than in previous studies in emerging countries that had sampled from all existing prisoners at a time. Affective disorders and suicide risk appear more prevalent than in admission studies conducted in Western high-income countries. Previous research may have systematically underestimated the extent of mental health problems in prisoners, which poses a major public health challenge in emerging countries.